الحماية المدنية للحيازة في التشريع الجزائري دراسة في قواعد القانون المدني و قانون الإجراءات المدنية و الإدارية - حدان, ياسين (جامعة الوادي University of Eloued, 2017)
الحيازة سلطة فعلية على الشيء يمارسها الشخص بنفسه أو بواسطة غيره، يمكن إثباتها بكل الطرق ومن بين ما تخلفه من أثار أنها تؤدي إلى اكتساب الملكية العقارية، ويظهر بمظهر صاحب الحق على الشيء، فالحيازة الصحيحة التي تؤدي إلى اكتساب الحق هي التي يجب أن يتوافر فيها السيطرة الفعلية لاكتساب الحق، ففي حالة انتفاء الركن المعنوي تسمى بالحيازة العرضية وحتى تكون الحيازة صحيحة وتنتج أثارها القانونية لا بد أن تكون خالية من العيوب كما يمكن أن تنتقل الحيازة إلى شخص أخر سواء كان خلفا عاما (ورثة) أو خاصا . فالحيازة مجرد حالة واقعية إلا أن في نظامها القانون وظائف خطيرة ودر فعال ونظرا لهذه الأهمية ولخطورة الآثار القانونية المترتبة عنها فقد تناول المشرع الجزائري في القانون المدني مجموعة الأحكام الموضوعية العامة للحيازة ثم تناول في قانون الإجراءات المدنية القواعد الإجرائية الخاصة لحمايتها عن طريق دعاوى الحيازة وهذا ما يجعل من النظام القانوني للحيازة في القانون الجزائري يفتقد إلى نظرية قانونية متكاملة . إن المشرع الجزائري لم يعرف الحيازة ضمن أحكام القانون المدني بخلاف بعض التشريعات المقارنة وذلك بحسب لصالحه كون من الأنسب من الناحية التشريعية أن لا تتناول القوانين تعريفات ويترك ذلك للفقه والقضاء والاجتهاد . الحيازة تقوم على ركنين أساسين هما الركن المادي والركن المعنوي، ويشكل الركن المادي مجموعة الأعمال المادية الظاهرة التي يقوم بها الحائز وتجعله يسيطر على العقار محل الحيازة والتي تصدر عادة ممن يتملك الشيء أو يملك عليه حقا من الحقوق، وقد يصح أن يباشر الحائز الركن المادي للحيازة بنفسه كما يباشــــرها بالوساطة وهــــو ما نصت عليه المــــادة ( 810 ق.م ) . إن المشرع الجزائري فرق بين الحيازة القانونية والحيازة العرضية فتقوم الأولى بتوافر الركنين ( المادي ، المعنوي ) وهي الحيازة التي يعتد بها قانون ويترتب عليها أثار هي: - الحيازة القانونية التي تتوفر فيها ركنيها وتستوفي شروطها تكون سببا من أسباب كسب الملكية العقارية بالتقادم . الحيازة قرنية على الملكية لكنها قرينة بسيطة قابلة للإثبات العكس فالحيازة المادية قرينة على الحيازة القانونية ، والحيازة القانونية قرينة على الملكية . أنه لما للحيازة من أهمية فقد أجمع القانون والفقه والقضاء على أن الحيازة في ذاتها بغض النظر عن الحق الذي تمثله هي جديرة بحماية القانون . قد تزول الحيازة بزوال الركنين معا أو بزوال أحدهما دون الآخر، كما قد تتعرض الحيازة إلى الغصب سواء بالقوة أو بالتحايل لذا استوجب المشرع تقرير حماية قانونية لها لدرء أي إعتداء تتعرض له وتتمثل هذه الحماية في تقرير دعاوى ثلاث هي دعوى منع التعرض ودعوى إسترداد الحيازة، دعوى وفق الأعمال الجديدة . ترفع هذه الدعاوى من الحائز أو المالك لذا أوجب المشرع عدم الجمع بين دعوى الحيازة ودعوى الملكية، كما تلزم هذه القاعدة كل من المدعي والمدعى عليه والقاضي، وأن الحكم الصادر في دعوى الحيازة له حجية أمام المحكمة التي تنظر دعوى الملكية . الاعتداء يستدعي السرعة في التدخل قصد وقفه لذا كان الفضاء الإستعجالي لما يوره من حماية هو المختص في دعوى وقف الأعمال الجديدة دون النظر إلى موضوع الحق . Possession of an actual power over a thing exercised by the person himself or by others, can be proved in all ways and from the effects that lead to the acquisition of real property, and appears as the right of the right, the right possession that leads to the acquisition of the right is where the control must be available The right to acquire the right. In the case of the absence of the moral element, it is called accidental possession and until the possession is valid and produces its legal effects, it must be free of defects, and the possession may be transferred to another person, whether he is a heir or private successor. The Algerian legislature, in civil law, dealt with the general set of substantive provisions of tenure and then dealt with the Code of Civil Procedure with the special procedural rules to protect it by means of property claims, Of the legal regime of tenure in Algerian law lacks an integrated legal theory. The Algerian legislator did not know possession within the provisions of the Civil Code, unlike some comparative legislation, according to his favor that it is more appropriate from the legislative point of view that the laws do not deal with definitions and leave it to jurisprudence, jurisprudence and jurisprudence. Possession is based on two basic pillars: the physical corner and the moral pillar. The physical element constitutes the set of material works which the holder makes and controls the property in possession which is usually issued by the person who owns the thing or owns the right. It also undertakes mediation, as stipulated in Article (810 BC). The Algerian legislator distinguishes between legal possession and accidental possession. The first is the availability of the two (physical, moral) assets, which are the possession of a law and have the following effects: - Legal possession in which the premises are available and meet their conditions is one of the reasons for the acquisition of real estate by prescription. Possession is corporeal on property, but it is a simple proof of proof. Physical possession is a presumption of legal possession, and legal possession is presumption of ownership. That the acquisition of importance, the law and jurisprudence and the elimination of the possession in itself regardless of the right it represents are worthy of the protection of the law. The possession may be removed by the passing of the two pillars together or by the demise of one of them without the other. The possession may also be subjected to rape, either by force or by fraud. The legislator therefore requires a legal protection report to prevent any attack. According to the new business. These claims are brought by the holder or the owner. The legislator therefore requires that the claim for possession and the claim of ownership be not combined. This rule is also required by the plaintiff, the defendant and the judge, and the judgment in the possession case is authoritative before the court hearing the property claim. Assault calls for speed in the intervention to stop it so was the space for the precaution of his protection is competent in the case of stopping new business without regard to the subject of right.
قانون عقاري
Keywords: الحيازة – العقار – الدعوى; Possession - property - suit